Settlement of Legal Disputes Against Rights Holders of the Famous Brand "Bensu" Based on the First to File Principle - Sina, Ammar Ibnu; Nekha, Asya; Deswanda, Corinna Nabilah; Pardomuan, Jones Benarto (Diponegoro Private Law Review, 2022)
In Indonesia there have been many legal cases related to famous trademark rights disputes, one clear example is the existence of a famous trademark dispute with the name bensu. This creates problems with Law Number 20 of 2016 concerning Brands and Geographical Indications which adheres to a constitutive system. The writing of this article aims to find out how the legal provisions and legal dispute resolution against the rights holders of the famous brand Bensu. The writing of this article uses a normative juridical approach with a descriptive method, and analysis using literature studies. The result of writing the article was that the lawsuit filed by Ruben Onsu against Jesy Handalim was not accepted by the panel of judges. And the trademark registration system in Indonesia adheres to the principle of first to file principal where the first registrant gets exclusive rights and legal protection.Keywords: First To File Principal, Famous Brand Rights, Legal Protection